Molecular cloning and primary structure of myelin-associated glycoprotein. - Arquint, M; Roder, J; Chia, L; Down, J; Wilkinson, D; Bayley, H; Braun, P; Dunn, R (1987)
Myelin-associated glycoprotein (MAG) may play a role in the cellular interactions leading to myelination. Using monoclonal antibodies and conventional antisera against MAG, we have isolated a cDNA clone from an expression library prepared from rat brain mRNA. The identity of the clone was confirmed by the exact match between its nucleotide sequence and two peptide sequences of 13 and 9 amino acids that we obtained by Edman degradation of two CNBr fragments of MAG. The cDNA clone hybridized to two size species of mRNA in rat approximately 3.5 kilobases in length. These mRNAs were present in brain but not liver and were expressed most abundantly at the time of active myelination (day 14). The mRNA for MAG was present at barely detectable levels in hypomyelinating jimpy mice compared to normal littermate controls. Therefore the MAG cDNA clone is both brain and myelin specific. DNA sequence analysis revealed that our MAG cDNA was derived from the same mRNA as clone p1B236, a randomly selected, brain-specific, partial cDNA isolated by Sutcliffe et al. [Sutcliffe, J. G., Milner, R. J., Shinnick, T. M. and Bloom, F. E. (1983) Cell 33, 671-682]. Analysis of the predicted protein sequence suggests that MAG has a long extracellular domain (499 amino acids), followed by a short transmembrane segment (20 amino acids) and an intracellular carboxyl-terminal domain (90 amino acids). The molecule has several glycosylation sites, three internal repeats homologous to a repeat in the neural cell adhesion molecule (N-CAM), and sites for phosphorylation near the carboxyl terminus. The primary structure reported here provides a molecular framework for further investigations into the function of the MAG molecule.